The Influence of Instagram Promotional Content on the Decision to Choose a Study Program at Hang Tuah University Pekanbaru - Risa Amalia; Rudi Rahman; Abdullah Mitrin; Thatalia Yunda (Semantik: Journal of Social, Media, Communication, and Journalism, 2026)
As a visual social media platform, Instagram exerts significant influence in conveying promotional messages, including within the context of higher education. Universitas Hang Tuah Pekanbaru actively utilizes this platform to introduce its study programs to the general public, particularly the digital-savvy younger generation. However, there is a lack of research specifically measuring the impact of Instagram promotional content on students' decisions regarding their choice of study program, particularly within the campus community. This study aims to analyze the extent to which Universitas Hang Tuah Pekanbaru's Instagram promotional content influences second-semester students' decisions in selecting a study program. The research focuses on second-semester students from the Communication Science, Information Systems, and Informatics Engineering study programs. The objective is to identify the visual factors, promotional messages, and content interactivity that shape their perceptions and decisions. A quantitative research method employing a survey approach was used. Data collection was conducted via an online questionnaire designed based on promotional content indicators and decision-making variables. The collected data were analyzed using descriptive and inferential statistical techniques, including regression and correlation analyses. The correlation analysis revealed a positive and significant relationship between Instagram promotional content and the decision to choose a study program (r = 0.61, p < 0.01). These findings support Social Media Marketing theory, which posits that engaging, informative, and relevant content can generate audience interest and influence their decisions.